‘Dirty Hands’: Guilt and Regret in Moral Reasoning - Gingles, Dallas J. (Studies in Christian ethics, 2023)
Nigel Biggar argues against ‘dirty hands’ reasoning for two reasons. The first is that dirty hands reasoning is paradoxical. The second is that ‘dirt’ in dirty hands is often—and wrongly—conceived as guilt. According to Biggar, the dirt should instead be understood as regret. In this article, I defend dirty hands reasoning against both criticisms. On the one hand, I argue that dirty hands reasoning is not necessarily paradoxical. On the other, I argue that, because guilt, more than regret, is meant to motivate the agent we should prefer a prima facie interpretation of the ‘dirt’ in dirty hands as guilt instead of regret.